Improved Poly (D, L‐lactide) nanoparticles‐based formulation for hair follicle targeting. (29th January 2015) - Fernandes, B.; Silva, R.; Ribeiro, A.; Matamá, T.; Gomes, A. C.; Cavaco‐Paulo, A. M.
Synopsis Objective Hair follicles are widely recognized as the preferential target and site of accumulation for nanoparticles after topical application. This feature is of particular importance for hair cosmetics, having the potential to refine the treatment of several hair follicle‐related disorders. The aim of this work was to improve the preparation of Poly (D, L‐lactide) (PLA) nanoparticles for in vivo follicular target and drug delivery. Methods Envisaging a future industrial scale‐up of the process, nanoprecipitation method was used to prepare PLA nanoparticles: the effect of several processing parameters on their properties was examined and the yield of nanoparticles formation determined. Encapsulation efficiencies and in vitro release profiles of lipophilic and hydrophilic model compounds were also assessed. In vitro cytotoxicity and ex vivo penetration studies were performed on a reference skin cell line (NCTC2455, human skin keratinocytes) and porcine skin, respectively. Results Using acetone : ethanol (50 : 50, v/v) as the solvent phase, 0.6% (w/w) of Pluronic® F68 as a surfactant agent and agitation to mix the solvent and non‐solvent phases, a monodispersed population of non‐cytotoxic spherical nanoparticles of approximately 150 nm was obtained. The yield of nanoparticles for this formulation was roughly 90%. After encapsulation of model compounds, no significant changes were found in the properties of particles and the entrapment efficiencies were above 80%. The release kinetics of dyes from PLA nanoparticles indicate an anomalous transport mechanism (diffusion and polymer degradation) for Nile Red (lipophilic) and a Fickian diffusion of first order for fluorescein 5(6)‐isothiocyanate (hydrophilic). Ex vivo skin penetration studies confirmed the presence of nanoparticles along the entire follicular ducts. Conclusions The optimized method allows the preparation of ideal PLA nanoparticles‐based formulations for hair follicle targeting. PLA nanoparticles can effectively transport and release lipophilic and hydrophilic compounds into the hair follicles, and the yields obtained are acceptable for industrial purposes.